Codon-optimized DsRed fluorescent protein for use in Mycobacterium tuberculosis - Paul Carroll; Julian Muwanguzi-Karugaba; Tanya Parish (BMC Research Notes, 2018)
Abstract Objective We have previously codon-optimized a number of red fluorescent proteins for use in Mycobacterium tuberculosis (mCherry, tdTomato, Turbo-635). We aimed to expand this repertoire to include DsRed, another widely used and flexible red fluorescent protein. Results We generated expression constructs with a full length DsRed under the control of one of three strong, constitutive promoters (Phsp60, PrpsA or PG13) for use in mycobacteria. We confirmed that full length DsRed (225 amino acids) was expressed and fluoresced brightly. In contrast to mCherry, truncated versions of DsRed lacking several amino acids at the N-terminus were not functional. Thus, we have expanded the repertoire of optimized fluorescent proteins for mycobacteria.